A Semantic Onomastic Analysis of Character and Place Naming in Zootopia (2016) - Mufidah, Betha Ayu; Jannah, Riha Zahrotul; Ramadhani, Qatrunnada Nafisa; Devi, Nadia Salsabila; Arianingsih, Aprilia (University of Surakarta, 2026)
This study considers how character and place names in the film Zootopia (2016) contribute to meaning, momentum, and plot in writing for animation. The aim of this essay is to discuss the onomastic role of anthroponyms (character names) and toponyms (place names) as far as character presentation and world-building are concerned. In this study, the research method employed was a qualitative descriptive with a Semantic Onomastics approach. The material from the film used on this occasion consisted of a number of characters and locations which were subject to analysis in the light of Ainiala, Saarelma and Sjoblom (2012)’s onomastic theory and Fillmore (2006)’s Frame Semantics. Analyses were conducted according to Spradley's stages of ethnographic analysis, which involved domain, taxonomy, component and cultural theme analysis. The findings of the current study have demonstrated that there is a high degree of semantic clarity present in the names within Zootopia, which are observed to be highly effective when it comes to creating a fictitious world full of context. To conclude, it can be stated that naming in Zootopia is a narrative strategy that serves to underscore the film's message of equality, tolerance and resistance to discrimination.